Development and validation of the Good Lives Questionnaire - Harper, Craig A. (Psychology, crime & law, 2021)
The Good Lives Model (GLM) is a framework of rehabilitation when working with individuals who have committed criminal offenses. However, its core assumptions (i.e. that the ‘good life’ is comprised of various universal primary human goods) have not been tested, and there is no standardized measure of these concepts. We used a large community sample (N = 1,309) to develop a measure of primary human goods. Our 100-item draft Good Lives Questionnaire (GLQ) was reduced to 35 items via exploratory principal components analysis (n = 900), with its five-factor structure supported by confirmatory factor analysis (n = 409). This structure runs counter to the existing scholarship related to the GLM, which proposes eleven primary human goods. We found each of our factors – ‘Inner Peace’, ‘Energy and Agency’, ‘Social Connectedness’, ‘Varied Leisure Activities’, and ‘Spirituality’ – to be differentially associated with measures of self-reported aggression, criminality, and delinquency, supporting its validity as a measure of crime- and delinquency-related constructs. They were also associated with measures of psychological wellbeing, personal agency, social connectedness, and personality. We discuss the future validation of the GLQ, as well as its potential utility in clinical and forensic settings. An open access preprint of this paper is available at https://psyarxiv.com/5trj9.